Quantitative Ontogeny of Murine Insulin-Like Growth Factor (IGF)-I, IGF-binding Protein-3 and the IGF-related Acid-labile Subunit - Hwang, David L. (2007)
OBJECTIVE: The mouse serves as an important model for insulin-like (IGF)-related research. However, lack of homologous mouse assays has prevented studies of the normal ontology of the murine IGF-system. Therefore, we developed and validated immunoaassays for murine IGF-I, IGFBP-3 and ALS and studied levels of these analytes in mice. METHODS: Using commercially available reagents, we developed and validated specific enzyme-linked immunosorbent assays (ELISAs) for murine IGF-I, IGFBP-3, and ALS. Levels of these analytes were measured in sera from CD-1 mice, male and female, sampled at 1, 2, 4, 8, 20 and 32 wks of age. In addition, sera from pregnant and post-partum CD-1 mice were also studied. RESULTS: Validation of specific ELISAs for murine IGF-I, IGFBP-3 and ALS are described; all 3 assays were highly sensitive, precise and accurate. As measured by our homologous ELISA, IGF-I levels (ng/mL, mean±SD) in male mice were relatively low at 1 wk (53±8), rising sharply to peak at 8 wks of age (636±48), and gradually declining thereafter, reaching 395±64 at 32 wks. IGF-I levels in non-pregnant female mice peaked at 4 wks of age (548±77) declined at 8 wks (417±61), then recovered to plateau at 539±78 and 535±88 at 20 and 32 wks, respectively. In male mice, trends in IGFBP-3 were similar to the patterns of IGF-I. However, in non-pregnant female mice, the IGFBP-3 levels declined relatively slowly after peaking at 4-weeks of age, unlike IGF-I levels during this period. ALS levels followed the same pattern as IGF-I in both sexes. IGF-I to IGFBP-3 molar ratios (percent) were similar between sexes, rising continuously with age: ~30% at 1 wk, 80% at 4 wks, 135% at 32 wks. IGF-I was reduced in 8 wk old mice in mid-pregnancy (354±75 vs 417±61 in non-pregnant 8 wk females), reaching a nadir in late-term (146±40), and only partially recovering in the postpartum period (239±23). IGFBP-3 was also lower in late-pregnancy (1245±100 vs 1925±439) and remained depressed post-partum. In contrast to IGF-I and IGFBP-3, ALS increased more than 3-fold in mid-pregnancy (12180±1641 vs 3741±910), followed by a 4-fold decrease in late-pregnancy (2964±489), recovering postpartum (6104±1178). CONCLUSIONS: We report the first ontological studies of IGF-I, IGFBP-3 and ALS in mice using newly-characterized sensitive, homologous immunoassays. Our results indicate that mice have a generally similar pattern in IGF-related axis components, with low levels early in life, increasing to peak during sexual maturation and declining thereafter. Significant gender differences in non-pregnant levels and dramatic changes during pregnancy were also found. Knowledge of the normal developmental changes in the murine IGF system and accurate tools for investigations of this system are a necessary foundation for research in this field.